Patella distal pole avulsion secondary to osteomyelitis in a healthy adult - Voon, V (Royal College of Surgeons, 2013)
Primary haematogenous patella osteomyelitis in an adult is a rare condition. Cases published in the literature relate predominantly to the paediatric population or are associated with risk factors such as intravenous drug abuse, human immunodeficiency virus and penetrating trauma. The rarity of this condition and its atypical presentation should be borne in mind while treating a patient with anterior knee pain. It is crucial to evaluate radiography of diagnostic quality carefully.